MYTHOLOGICAL CHARACTERS IN TRADITIONAL BELIEFS OF THE GUMBET AVARS (SECOND HALF OF THE XX – THE BEGINNING OF THE XXI CENTURY) - Seferbekov, Ruslan Ibragimovic; Razahanov, Said Seferbekovic; Galbacev, Surhaj Magomedovic (History, Archeology and Ethnography of the Caucasus, 2022)
Based of field material, using general and specific methods of historical science, the article describes mythological characters of the former pantheon and pandemonium of the Gumbet Avars: personified heavenly bodies and atmospheric phenomena, mummers and dolls, patrons of wild animals and hunting, supreme deities; “house snakes”, demons intruding the dwelling and strangling a sleeping person, antagonists of pregnant women, shaitans. The sources for these characters are folklore (mythology, oaths, good wishes, sayings), vocabulary and phraseology, calendar, family and social rituals, customs and beliefs. With the adoption of Islam, most of the mythological characters of Gumbets’ pagan pantheon and pandemonium were forgotten, and some of the surviving ones, due to the stability of traditional religious beliefs in the spiritual culture of the ethnos, were Islamized and took the form of syncretic, “everyday Islam”. Some of the Islamized mythological characters have become mediators between man and the God, which contradicts the doctrine of Islam. A significant role in consolidation of pre-monotheistic beliefs in the spiritual culture of the Avars and other peoples of Dagestan in Soviet and modern times was played by the healthy conservatism inherent in all Dagestanis and the peculiarities of their mentality – adherence to traditional values. Such a circumstance inspires some confidence in the preservation of their religious, cultural and ethnic identity in the era of globalization.